2016
DOI: 10.1021/acs.chemmater.5b03968
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar Charge Transport in Isoindigo-Based Donor–Acceptor Polymers

Abstract: A series of donor−acceptor isoindigo (iI)-based copolymers synthesized with increasing numbers of thiophene rings in the repeat unit (from zero to three thiophene rings, including silole and germole-bridged fused bithiophene units) is applied toward solutionprocessed OFET devices. Differential pulse voltammetry on thin films of the polymers recorded LUMO energy levels confined within a 0.1 eV range around 3.9 eV, while their bandgaps are estimated at 1.5 to 1.7 eV. The interchain π-stacking distance of each sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 73 publications
5
81
0
Order By: Relevance
“…To date, almost all the reported ambipolar transport CPs with both hole and electron mobility (μ h and μ e ) >1 cm 2 V −1 s −1 were built with diketopyrrolopyrrole (DPP), and the ambient‐stable n‐type CPs with μ e > 1 cm 2 V −1 s −1 were based on either naphthalene diimide or benzodifurandione derivatives . On the other hand, isoindigo (IID) has been recognized as an ideal electron‐deficient building block for making D–A CPs soon after its first use in the design of donor materials for organic solar cells by Reynolds and co‐workers and IID‐based CPs have been widely used as semiconducting materials in OFET and organic photovoltaic devices . Ambipolar CPs based on IID have been demonstrated by introducing electron withdrawing groups on IID unit or using different comonomers .…”
Section: Ofet Device Performance Data Of the Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, almost all the reported ambipolar transport CPs with both hole and electron mobility (μ h and μ e ) >1 cm 2 V −1 s −1 were built with diketopyrrolopyrrole (DPP), and the ambient‐stable n‐type CPs with μ e > 1 cm 2 V −1 s −1 were based on either naphthalene diimide or benzodifurandione derivatives . On the other hand, isoindigo (IID) has been recognized as an ideal electron‐deficient building block for making D–A CPs soon after its first use in the design of donor materials for organic solar cells by Reynolds and co‐workers and IID‐based CPs have been widely used as semiconducting materials in OFET and organic photovoltaic devices . Ambipolar CPs based on IID have been demonstrated by introducing electron withdrawing groups on IID unit or using different comonomers .…”
Section: Ofet Device Performance Data Of the Polymersmentioning
confidence: 99%
“…On the other hand, isoindigo (IID) has been recognized as an ideal electron‐deficient building block for making D–A CPs soon after its first use in the design of donor materials for organic solar cells by Reynolds and co‐workers and IID‐based CPs have been widely used as semiconducting materials in OFET and organic photovoltaic devices . Ambipolar CPs based on IID have been demonstrated by introducing electron withdrawing groups on IID unit or using different comonomers . Particularly, Pei and co‐workers found that introducing two fluorine (F) or chlorine (Cl) atoms in IID core could lower the frontier molecular orbital energy levels and promote the self‐organization ability of the polymers, resulting in ambipolar CPs with μ e up to 0.66 cm 2 V −1 s −1 under the ambient conditions .…”
Section: Ofet Device Performance Data Of the Polymersmentioning
confidence: 99%
“…This structure consists of two isoindigo units joined by a single bond at their 6 positions . Shortly before we started this work, others had elucidated structure‐property relationships relating the number of donor units in a donor‐acceptor copolymer to optoelectronic properties such as carrier mobility and optical band gap . We felt that this isoindigo dimer would be an effective way to develop similar relationships from the perspective of the acceptor.…”
Section: Isoindigo Derivativesmentioning
confidence: 99%
“…The fill factor also increased slightly, from 0.63 to 0.69, helping to offset the decrease in V oc from 0.89 to 0.70 V. The good performance of 4 : PC 71 BM devices was an important milestone for isoindigo‐based polymers, and prompted further isoindigo‐oligothiophene copolymer research. Copolymers of isoindigo and oligothiophenes (e. g., 5 and 6 ) would go on to become some of the most popular isoindigo‐based polymer semiconductors owing to their ease of synthesis, excellent optoelectronic properties, and OPV performance …”
Section: Introductionmentioning
confidence: 99%
“…[38,39] To probe carrier transport across optimized BHJ active layers with SM1 and SM2, we turned to space charge limited current (SCLC) mobility measurements (cf. [38,39] To probe carrier transport across optimized BHJ active layers with SM1 and SM2, we turned to space charge limited current (SCLC) mobility measurements (cf.…”
Section: Device Testing and Characterizationsmentioning
confidence: 99%